2007
DOI: 10.1007/s10620-007-9931-0
|View full text |Cite
|
Sign up to set email alerts
|

CV-11974, angiotensin II type I receptor antagonist, reduces the severity of indomethacin-induced rat enteritis

Abstract: The aim of the present study was to examine the effect of angiotensin II type I receptor antagonist, CV-11974, on indomethacin-induced small intestinal injury in rats. Single administration of indomethacin provoked severe inflammatory lesions in the small intestine. The levels of thiobarbituric acid-reactive substances (TBARS), myeloperoxidase (MPO) activities and cytokine-induced neutrophil chemoattractant-1 (CINC-1) in the intestinal mucosa significantly increased in the indomethacin-treated group compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…On the other hand, support for the possibility that H. pylori infection induces mucosal AT1R expression that increases the infiltration of PMNs is that AT1R antagonists decrease neutrophil infiltration in a rat model of stress induced gastric injury, as well as in a rat model of indomethacin induced enteritis [4,32]. We found AT1R on the endothelial cells of vessels located in the gerbil mucosa, and Matsuo et al .…”
Section: Discussionsupporting
confidence: 68%
“…On the other hand, support for the possibility that H. pylori infection induces mucosal AT1R expression that increases the infiltration of PMNs is that AT1R antagonists decrease neutrophil infiltration in a rat model of stress induced gastric injury, as well as in a rat model of indomethacin induced enteritis [4,32]. We found AT1R on the endothelial cells of vessels located in the gerbil mucosa, and Matsuo et al .…”
Section: Discussionsupporting
confidence: 68%
“…(24) Okuda et al, indicated that the microvascular disturbance induced by indomethacin may be associated with chemokine production related to the interaction between the angiotensin II and angiotensin II Type I receptor. (25) In the present study, indomethacin administration led to rise of gastric CINC-1 level. Candesartan (2 and 5 mg/ kg) reduced the CINC-1 level in the stomach homogenate of indomethacin-treated group.…”
Section: Discussionsupporting
confidence: 55%
“…Clearly, ACE-I had a very strong benefit in protecting the barrier function of the epithelium; and this action was far superior to that seen with prednisolone. This may be how the use of angiotensin II blockade mediates its action in an indomethacin intestinal injury model [48]. It is also possible that the use of ACE-I may be used chronically in IBD patients to maintain barrier function, and thus prevent recurrent episodes of acute inflammation.…”
Section: Discussionmentioning
confidence: 99%